Determining the feasibility of implementing a construction project at the pre-investment stage (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The present study is aimed at determining the feasibility of implementing a construction project at the stage of re-investment based on the principles of development in Ukraine. The study included a survey that helped identify the key factors of investment budget overruns, as well as economic modelling of construction projects, which helped identify the relationship between risks and financial performance. The data obtained were analysed using correlation analysis to assess the impact of development principles on the effectiveness of management decisions. The study found that a significant number of construction projects face risks that exceed the originally planned budget. The main factors affecting budget overruns were changes in the regulatory environment, underestimation of materials and labour costs, and unpredictable external economic factors. Economic modelling has shown that companies that implement development principles can reduce the risk of budget overruns compared to those that do not. This indicates a significant positive impact of development on management decisions. The correlation analysis revealed a strong correlation between the implementation of development principles and the growth of return on investment. Companies that have implemented these principles have recorded an increase in profitability compared to similar projects that have not used these approaches. The application of development principles helped to make more informed investment decisions. The results of the study highlight the importance of integrating development principles into the management strategies of construction companies.
Keywords: Economic factors; Flexible management; Management decisions; Planned budget; Profitability; Risk